2012
DOI: 10.1002/aic.13766
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the heating effects of microwave discharge caused by metals

Abstract: The heating effects of discharge triggered at the appearance of metals are important under microwave irradiation but special studies have rarely been carried out. In our experiments, the heat generation was successfully isolated by embedding metal in quartz sand and measured through an indirect calorimetric method. All the experiments and analyses indicate that the discharge triggered by metals under microwave irradiation has remarkable heating effects. The microwave power, irradiation time, metal amount, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…As a direct consequence of these discharges, considerable heat is produced, leading to the formation of high-temperature local hotspots. Wang and co-author reported the heat produced by discharge can melt the metal terminals (as shown in Figure 4 ) and the energy conversion efficiency from the electric energy to heat by microwave-metal discharge can amount to 20%–60% during the microwave irradiation process, as shown in Figure 5 [ 96 , 97 ]. One the other hand, at a microscopic level, these discharge are actually plasma [ 12 ].…”
Section: Effects Of Microwave-metal Interactionsmentioning
confidence: 99%
“…As a direct consequence of these discharges, considerable heat is produced, leading to the formation of high-temperature local hotspots. Wang and co-author reported the heat produced by discharge can melt the metal terminals (as shown in Figure 4 ) and the energy conversion efficiency from the electric energy to heat by microwave-metal discharge can amount to 20%–60% during the microwave irradiation process, as shown in Figure 5 [ 96 , 97 ]. One the other hand, at a microscopic level, these discharge are actually plasma [ 12 ].…”
Section: Effects Of Microwave-metal Interactionsmentioning
confidence: 99%
“…Our research group has studied the heating effects associated with microwave-metal discharges and found that the energy conversion ratio from electrical energy to heat can reach as high as 30% [28]. Based on the unique material characteristics of WPCBs and the discharge properties of metals, we have previously established that microwave-induced pyrolysis holds promise as a way to process WPCBs [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also some natural drawbacks of microwave heating: (a) When heating materials by microwave, there exist "hot spots" and thermal runaway problems in the system temperature [7], which will cause degradation of the processing materials [8][9][10][11] and even cause burning and explosion of the microwave reactor and reactants [12,13]. (b) When dealing with numerous solid materials, their stacking in the heating cavity can easily result in some sharp edges, tips or submicroscopic irregularities, which may lead to electric sparks or electric arcs [14,15]. These electric discharges will affect the heating process and the product composition, and lead to safety problems when dealing with materials that have a low flashing point or in high temperature conditions [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…For studies on the electric discharge phenomena, related research has focused on microwave discharges in sintering of powdered metals. Attention is mainly paid to factors that influence the intensity and frequency of microwave discharges, such as the magnetron output power [14,33], the size, amount, conductivity, morphology and surface conditions of the metal [14,[33][34][35] and the dielectric properties of the surrounding medium [15,[35][36][37]. The lack of comprehensive consideration of the heating uniformity and safety of microwave heating solid stack materials has hindered the further application of microwave heating.…”
Section: Introductionmentioning
confidence: 99%